KOMUNIKASI MEDIA ONLINE PENGUSAHA MILENIAL DALAM MEMBANGUN PERSONAL BRANDING DI ERA DIGITAL - Dewi Rachmawati; Lestari Nurhajati (Metacommunication: Journal of Communication Studies, 2019)
ABSTRACT Scientists who use cohort generation (generation cohorts) to classify subjects by age group, strongly believe in differences in attitudes, behaviors and communication in each generation. Millennials in the age range of 23-39 (born 1980-1995) tend to be depicted as relying heavily on communication based on internet technology. This situation certainly causes significant communication changes, including when these millennials become entrepreneurs, inevitably they will rely on communication via online media. In 2018, several rows of Indonesian millennials entered the ranks of successful Asian entrepreneurs under the age of 30. This phenomenon certainly becomes interesting to study about how the use of online media by young entrepreneurs as a means of their communication with the public. This study aims to find out how the personal branding of millennial entrepreneurs is built with communication via online media. The personal branding study that is often used as a guideline is the Eight Laws of Personal Branding concept, which is a personal branding strategy that emphasizes the side; specialization, leadership, personality, distinctiveness, visibility, unity, persistence, and goodwill. This study uses the content analysis (content analysis) approach to 5 online media (Instagram, Facebook, Twitter, Youtube, LinkedIn and Website / blog) owned by 5 millennial entrepreneurs (Dian Pelangi, Fransisca Hadiwidjana, Talita Setyadi, Rorian Pratyaksa, and Stanislaus Tandelilin) within 1 year (1 January 2018 - 31 December 2018). The results of this study indicate that the effort to build personal branding on each of the online media owned, is only attached to the figure of Dian Pelangi, who is very active in using all lines of social media. While the other 4 subjects actually did not all actively utilize the social media / online media they had..Keywords:  online media communication, millennials, personal branding, millennial entrepreneurs, digital era.  ABSTRAK Ilmuwan yang menggunakan cohort generation (generasi kohort) untuk menggolongkan subyek berdasarkan kelompok umur, sangat mempercayai adanya perbedaan sikap, perilaku dan komunikasi pada tiap generasi. Generasi milenial dalam rentang usia 23-39 (lahir 1980-1995) cenderung digambarkan sangat mengandalkan komunikasi berbasis penggunaan teknologi internet. Situasi ini tentu menyebabkan perubahan komunikasi yang signifikan, termasuk ketika para milenial ini menjadi pengusaha, mau tidak mau mereka akan mengandalkan komunikasi via media online. Tahun 2018 lalu beberapa deretan pengusaha milenial Indonesia masuk dalam jajaran pengusaha sukses Asia di bawah usia 30 tahun. Fenomena ini tentu menjadi menarik untuk diteliti tentang bagaimana penggunaan media online para pengusaha muda ini sebagai sarana komunikasi mereka dengan publik. Penelitian ini bertujuan untuk mengetahui bagaimana personal branding para pengusaha milenial dibangun dengan komunikasi via media online. Kajian personal branding yang sering dijadikan pedoman adalah konsep Eight Laws of Personal Branding, yakni strategi personal branding yang menekankan pada sisi; spesialisasi, kepemimpinan, kepribadian, kekhasan, terlihat, Kesamaan antara yang terlihat dan tak terlihat, kegigihan dan itikad baik. Penelitian ini menggunakan pendekatan penelitian content analysis (analisis isi) atas 5 media online (Instagram, Facebook, Twitter, Youtube, LinkedIn dan Website/blog) yang dimiliki oleh 5 pengusaha milenial (Dian Pelangi, Fransisca Hadiwidjana, Talita Setyadi, Rorian Pratyaksa, dan Stanislaus Tandelilin) dalam kurun waktu 1 tahun (1 januari 2018 - 31 Desember 2018). Hasil dari penelitian ini menunjukkan bahwa upaya membangun personal branding pada masing-masing media online yang dimiliki, hanya melekat pada sosok Dian Pelangi, yang sangat aktif menggunakan semua lini media sosialnya. Sementara ke 4 subyek lainnya justru tidak semuanya aktif memanfaatkan media sosial/ media online yang dimilikinya..Kata Kunci: komunikasi media online, milenial, personal branding, pengusaha milenial, era digital.